Sense of country: General and specific factors covary with social identification and predict emigration plans - Kolesovs, Aleksandrs (Frontiers in Psychology, 2022)
Theoretical analyses of person–environment interaction describe complex models, addressing different levels of social systems, while models of the sense of community provide a base for transferring views of this interaction to the national level. This paper presents two studies that explored the structure of the sense of country and its relation to emigration plans and social identification. Study 1 involved 1005 adults from Latvia. The Sense of Country Inventory (SOCI) included influence, opportunities, belonging, and spatiotemporal commitment as the components of this sense. The bifactor model demonstrated the best fit and confirmed the general factor, integrating components of the sense of country, and specific factors, emphasizing its complexity. The validation demonstrated that the general sense of country is the main negative predictor of emigration plans. Study 2 included 247 participants who completed the SOCI and Identification With All Humanity Scale. Correlating with national identification, the sense of country negatively predicted emigration plans that reflected the social identity continuity pathway. In turn, a negative relationship between the sense of country and global identification, which positively predicted emigration plans, revealed a social identity gain pathway. Together, the studies present the integrative nature of the sense of country and its links to emigration plans and national and global social identification.